Groundwater potential zone assessment in Lumding, Assam, India, utilizing NASA’s space-based satellite sensors and a multi-criteria decision-making technique - DEY, RUPAK; SHARMA, SEEMA (Journal of Soil and Water Conservation, 2022)
Groundwater is one of the most important natural resources stored under the earth’s surface via infiltration and various rock strata. Groundwater supplies over 30% of fresh water globally, with 65% used for agricultural irrigation, 25% for drinking water, and the remaining 10% used for industrial water. Unsustainable groundwater consumption is becoming more visible and a major worry for many developing countries. In India, water resources are unevenly distributed in both the geographic and temporal domains. In groundwater exploration, integrated remote sensing and geographical information system (GIS) has become an important way to explore groundwater resources, assessing, monitoring, and conserving them. For the investigation of groundwater resources in the study area, an integrated approach of remote sensing (RS) and geographic information system (GIS) was used to create seven thematic layers: landuse/ landcover (LU/LC), geology, geomorphology, drainage density, lineament density, slope (Digital Elevation Model), and lithology. To construct the final groundwater potential zonation map, the thematic layers were combined using an AHP weighted overlay approach. The potential ground water regions were divided into five zones. 1-Very low, 2-low, 3-medium, 4-high, and 5-very high. According to the groundwater potential zones, 0.95 and 6.93 percent of the studied regions, however, have very high and high potentiality. Medium potential groundwater zones cover 22.44 percent of the land and are found all across the area. On the other side, low to extremely low potential groundwater issues occur in around 24.24 and 7.92 percent of regions, respectively. Surface topography, slope, underlying rock composition, and lineaments all impact groundwater recharge and availability as they influence porosity, permeability, and rate of infiltration. The groundwater potential zonation map created in this research will help engineers, planners, and policymakers find optimal sites for water exploration and to implement the sustainable exploitation.